2018
DOI: 10.3389/fimmu.2018.01945
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Proteins Containing MAP-1 and Functional Domains of C4b-Binding Protein Reveal Strong Complement Inhibitory Capacities

Abstract: The complement system is a tightly regulated network of proteins involved in defense against pathogens, inflammatory processes, and coordination of the innate and adaptive immune responses. Dysregulation of the complement cascade is associated with many inflammatory disorders. Thus, inhibition of the complement system has emerged as an option for treatment of a range of different inflammatory diseases. MAP-1 is a pattern recognition molecule (PRM)-associated inhibitor of the lectin pathway of the complement sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 60 publications
(88 reference statements)
3
22
0
Order By: Relevance
“…It has been reported that MAP‐1 forms calcium‐dependent homodimers (13) and that this characteristic can be employed to dimerize MAP‐1–containing engineered complement inhibitors (25, 26). To ensure that the addition of CD35 and CD55 functional domains in the C terminus of MAP‐1 did not hinder its ability to dimerize, we subjected MAP‐1:CD35 1–3 and MAP‐1:CD55 1–4 to SEC under physiologic concentrations of calcium and in the presence of the calcium chelator EDTA.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that MAP‐1 forms calcium‐dependent homodimers (13) and that this characteristic can be employed to dimerize MAP‐1–containing engineered complement inhibitors (25, 26). To ensure that the addition of CD35 and CD55 functional domains in the C terminus of MAP‐1 did not hinder its ability to dimerize, we subjected MAP‐1:CD35 1–3 and MAP‐1:CD55 1–4 to SEC under physiologic concentrations of calcium and in the presence of the calcium chelator EDTA.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the in vitro inhibitory activity of the chimeric proteins in the LP using an established ELISA‐based setup (26). We incubated the chimeric proteins on an MBL‐mannan‐coated plate before adding MBL‐defect serum as complement source.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations